2017
DOI: 10.1021/jacs.7b07223
|View full text |Cite
|
Sign up to set email alerts
|

Phase Segregation in Cs-, Rb- and K-Doped Mixed-Cation (MA)x(FA)1–xPbI3 Hybrid Perovskites from Solid-State NMR

Abstract: Hybrid (organic–inorganic) multication lead halide perovskites hold promise for a new generation of easily processable solar cells. Best performing compositions to date are multiple-cation solid alloys of formamidinium (FA), methylammonium (MA), cesium, and rubidium lead halides which provide power conversion efficiencies up to around 22%. Here, we elucidate the atomic-level nature of Cs and Rb incorporation into the perovskite lattice of FA-based materials. We use 133Cs, 87Rb, 39K, 13C, and 14N solid-state MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
445
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(474 citation statements)
references
References 49 publications
26
445
3
Order By: Relevance
“…We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far. We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far.…”
Section: Structural Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far. We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…[16,26,27] Since the A/FA and A′/FA phases contain a 3D perovskite phase, 14 N MAS NMR can yield information on whether or not this phase is microscopically modified by the presence of the spacer. In the case of 3D perovskites, 14 N MAS NMR spectra feature a spinning sideband (SSB) pattern that corresponds to the central cation reorienting on the picosecond timescale within the cubooctahedral cavity.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…Being too small to be inserted in the perovskite framework, it has been suggested that they can sit at the interstitial sites of the perovskite lattice, inhibiting iodine vacancies migration [26] (see section 3). Discussion on this is still open: recent solid state NMR studies have proven that neither Rb + nor K + can enter the perovskite lattice [27]: they rather segregate into phases such as δ-Cs 0.5 Rb 0.5 PbI 3 . On the other side, Li et al [28] showed that small cations such as Li + and Na + can migrate through the perovskite, possibly influencing the long term stability of the devices.…”
Section: Oxygen and Lightmentioning
confidence: 99%
“…The MHP crystalline structure is usually depicted by the general formula ABX 3 , where A and B are cations while X stands for an anion . The A‐site monovalent cations can be organic (e.g., methylammonium (MA) CH 3 NH 3 + , or formamidinium (FA) CH(NH 2 ) 2 + ), inorganic (e.g., Cs + , or Rb + ), or organic–inorganic mixtures . The B‐site divalent metal cations are usually Pb 2+ , Sn 2+ , Ge 2+ , Cu 2+ , or Bi 2+ or their mixtures, whereas X represents a monovalent halide anion (e.g., Cl − , Br − , or I − ).…”
Section: Metal Halide Perovskites and Synthesismentioning
confidence: 99%